Hubungan Pengetahuan dan Sikap Terhadap Rokok Dengan Kebiasaan Merokok Siswa SMP di Kabupaten Bandung - Ageng saepudin kanda S; Silven yonathan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This type of research is observational analytic in the form of a cross-sectional study design. The population in this study were all junior high school students in Bandung Regency for the 2023/2024 academic year. The total sample was 30 students taken using Cluster Sampling and Simple Random Sampling. Data was collected by questionnaire. Data processing was carried out computerized and analyzed using the Chi-Square test at α=0.05. Results: 32.30% of students were smokers, 10.4% had low knowledge, and 7.3% had negative attitudes. There is no significant relationship between knowledge (p=1,000) and attitude (1,000) with smoking habits among junior high school students in Bandung Regency. Conclusion: there is no significant relationship between knowledge (p=0.155) and attitudes towards smoking among junior high school students in Bandung Regency. It would be best to educate junior high school students in Bandung Regency about the chemicals in cigarettes and cigarette smoke and their impact on health.